APPLICATION OF INNOVETIVE TECHNOLOGIES AS A WAY OF TEACHING STUDENTS TO IMPROVE THE QUALITY OF EDUCATION - Ruzan E. Mirzahanyan (Статистика и экономика)
In the educational environment developedmany unique teaching methods withinnovative technology. The author has applied an integrated approachto the course «Operations Researchand Optimization Techniques». Theharmonious development of thecompetency model is advisable to use avariety of activities: reports, role-playingand simulation games, case study.